The effects of multi-sport intervention on agility performance among young athletes - Jorrye Jakiwa; Shahrulfadly Rustam; Siti Azilah Atan; Mohd Syrinaz Azli; Ahmad Bisyri Husin Musawi Maliki; Ahmad Nadzmi; Ahmad Fadly Abd Rahman; Md Safwan Samsir (Horizon Research Publishing, 2023)
This study aimed to investigate the effect of a multi-sport intervention on the agility performance of young athletes aged 13 to 14 years old. A total of 40 athletes participated voluntarily in the study and were randomly assigned to either the experimental group 1 (n=20) or the multi-sport training group (n=20) using a quasi-experimental method. The experimental group 2 (EXP2) underwent multi-sport training which included football, futsal, sepak takraw, volleyball, basketball, and netball, while the experimental group 1 (EXP1) only received training in football and futsal. The Quadrant Jump Test was used to measure agility performance three times: pre-test (baseline), post-test 1 (week 6), and post-test 2 (week 12). The results showed that the multi-sport training group led to a significant improvement in agility performance, as indicated by a two-factor repeated measures ANOVA (F(1, 19) = 10214.43, p < .001) and significant main effects of both intervention and time on agility performance (F(1, 19) = 28.65, p < .001 and F(1, 19) = 418.61, p < .001, respectively). In conclusion, the multi-sport intervention proved to be beneficial for young athletes and should be included in the training routines of children and adolescents at all levels of sports academies and development